2015
DOI: 10.1186/s13012-016-0399-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated knowledge translation (IKT) in health care: a scoping review

Abstract: BackgroundIntegrated knowledge translation (IKT) refers to collaboration between researchers and decision-makers. While advocated as an approach for enhancing the relevance and use of research, IKT is challenging and inconsistently applied. This study sought to inform future IKT practice and research by synthesizing studies that empirically evaluated IKT and identifying knowledge gaps.MethodsWe performed a scoping review. We searched MEDLINE, EMBASE, and the Cochrane Library from 2005 to 2014 for English langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
555
3
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 443 publications
(580 citation statements)
references
References 51 publications
(62 reference statements)
9
555
3
13
Order By: Relevance
“…A 2016 scoping review of IKT studies reported that lack of skill or understanding of IKT processes was a barrier to the process 2. This paper, grounded in the literature, our research and experience, updates developments in the field of IKT, and offers a deeper analysis of the IKT approach in practice and policy-oriented health research.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…A 2016 scoping review of IKT studies reported that lack of skill or understanding of IKT processes was a barrier to the process 2. This paper, grounded in the literature, our research and experience, updates developments in the field of IKT, and offers a deeper analysis of the IKT approach in practice and policy-oriented health research.…”
Section: Introductionmentioning
confidence: 73%
“…IKT is not what is sometimes called team science2 3 for which a multidisciplinary group of researchers, sometimes across a large geographical area, is brought together to partner for the purposes of sharing research resources, training or expertise. IKT differs from team science in that its core aim is to develop research questions that are informed by needs in practice or policy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Patients and service leaders can help researchers to clarify goals, gather new evidence in real-life complex systems, and identify appropriate approaches for conducting and evaluating planned changes. 23 Such evaluations may be formative, using findings to optimise implementation, or summative, producing evidence of ultimate impact or both.…”
Section: Enhancing Feedback By Harmonising Outcome Measuresmentioning
confidence: 99%
“…OTN’s involvement in an advisory capacity increases the likelihood that the study results will have a future impact on health system policy. This engages the principles of integrated knowledge translation to collaboratively produce knowledge [16], with the aim of optimizing health care delivery and associated clinical outcomes. The study is funded by Canada Health Infoway.…”
Section: Methodsmentioning
confidence: 99%